2010
DOI: 10.1177/0956797610367751
|View full text |Cite
|
Sign up to set email alerts
|

Early Occipital Sensitivity to Syntactic Category Is Based on Form Typicality

Abstract: Syntactic factors can rapidly affect behavioral and neural responses during language processing, however, the mechanisms that allow this rapid extraction of syntactically relevant information remain poorly understood. We address this issue using magnetoencephalography, and find that an unexpected word category (like The recently princess…) elicits enhanced activity in visual cortex as early as 120ms, as a function of the compatibility of a word's form with the form properties associated with a predicted word c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
163
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(174 citation statements)
references
References 31 publications
(55 reference statements)
8
163
1
2
Order By: Relevance
“…For example, listeners are more likely to direct their eye-gaze to a picture of an edible object (e.g., a cake) when they hear the beginning of an utterance like 'The boy will eat…' compared to a neutral utterance such as 'The boy will move…' (Altmann & Kamide, 1999). Further, much evidence has suggested that comprehenders compute rich expectations about upcoming inputs at multiple levels of representation (syntactic: Ilkin & Sturt, 2011;Lau, Stroud, Plesch, & Phillips, 2006;Levy, Fedorenko, Breen, & Gibson, 2012;Omaki et al, 2015;Staub & Clifton, 2006;Wicha et al, 2004;Van Berkum et al, 2005;Yoshida, Dickey, & Sturt, 2013;lexico-semantic: Federmeier & Kutas, 1999;Kutas & Hillyard, 1984;Otten & Van Berkum, 2008;Szewczyk & Schriefers, 2013; phonological and orthographic: Delong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkanen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Farmer, Yan, Bicknell, & Tanenhaus, 2015;Kim & Lai, 2012;Laszlo & Federmeier, 2009). Here, we operationally define 'prediction' as the pre-activation of stored representations before the bottom-up input is encountered, and we will make no a priori assumptions regarding the nature of the mechanisms involved (e.g., whether they are automatic or controlled).…”
Section: Prediction In Language Comprehensionmentioning
confidence: 99%
“…For example, listeners are more likely to direct their eye-gaze to a picture of an edible object (e.g., a cake) when they hear the beginning of an utterance like 'The boy will eat…' compared to a neutral utterance such as 'The boy will move…' (Altmann & Kamide, 1999). Further, much evidence has suggested that comprehenders compute rich expectations about upcoming inputs at multiple levels of representation (syntactic: Ilkin & Sturt, 2011;Lau, Stroud, Plesch, & Phillips, 2006;Levy, Fedorenko, Breen, & Gibson, 2012;Omaki et al, 2015;Staub & Clifton, 2006;Wicha et al, 2004;Van Berkum et al, 2005;Yoshida, Dickey, & Sturt, 2013;lexico-semantic: Federmeier & Kutas, 1999;Kutas & Hillyard, 1984;Otten & Van Berkum, 2008;Szewczyk & Schriefers, 2013; phonological and orthographic: Delong et al, 2005;Dikker, Rabagliati, Farmer, & Pylkkanen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Farmer, Yan, Bicknell, & Tanenhaus, 2015;Kim & Lai, 2012;Laszlo & Federmeier, 2009). Here, we operationally define 'prediction' as the pre-activation of stored representations before the bottom-up input is encountered, and we will make no a priori assumptions regarding the nature of the mechanisms involved (e.g., whether they are automatic or controlled).…”
Section: Prediction In Language Comprehensionmentioning
confidence: 99%
“…One alternative interpretation argues that these early components instead index mismatches between predicted sensory input and actual sensory input (e.g., the wordform by is visually surprising in a context in which a noun was expected, because this wordform is only used as a preposition, Dikker, Rabagliati, Farmer, & Pylkkänen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009;Kim & Lai, 2012); under this account, the ERP response to by does not reflect combinatorial syntactic processing, but a sensory prediction error. A second, more deflationary account, has argued that early ERP responses to ungrammatical words might also result from artefacts caused by how ERP data are baseline corrected (Steinhauer & Drury, 2012).…”
Section: The Potential For False Positives In the Breaking Cfs Paradigmmentioning
confidence: 99%
“…Recent ERP and MEG studies indicate substantially earlier contact (∼100-200 msec) between word form analysis and lexical semantic processing (e.g., Dikker & Pylkkanen, 2011;DellʼAcqua et al, 2010;Dambacher, Rolfs, Göllner, Kliegl, & Jacobs, 2009;Penolazzi, Hauk, & Pulvermüller, 2007;Hauk, Davis, Ford, Pulvermüller, & Marslen-Wilson, 2006;Sereno, Brewer, & OʼDonnell, 2003) or lexical syntactic processing (Dikker, Rabagliati, Farmer, & Pylkkänen, 2010;Dikker, Rabagliati, & Pylkkänen, 2009). , for instance, found that sentence context modulated the ERP elicited by ambiguous words 132-192 msec after stimulus onset.…”
Section: Introductionmentioning
confidence: 99%
“…Several accounts of these effects involve context-driven predictions about word forms, allowing rapid sensitivity to word form inputs that deviate from predictions (Dikker et al, 2009(Dikker et al, , 2010Dambacher et al, 2009;Solomyak & Marantz, 2009). This recurrent processing view is consistent with growing evidence that language processing operates in an anticipatory manner, using context to predict the linguistic input at multiple levels (e.g., Altmann & Mirković, 2009;DeLong, Urbach, & Kutas, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation